Health promotion programs in higher education: integrative review of the literature - Fernanda Maria Príncipe Bastos Ferreira; Irma da Silva Brito; Margarida Reis Santos
ABSTRACT Objective: to characterize the interventions of health promotion programs implemented in Health Promoting Universities; to analyze the results of the interventions of health promotion programs. Method: integrative review carried out in EBSCO, PubMed, SciELO, Scopus and Web of Science. Articles published between 2000 and 2014 were selected, with evidence of health promotion intervention programs and evaluation of results. Results: 17 articles were included. The health promotion programs aimed at increasing the welfare of students, with an emphasis on physical activity, sexual health and on improving the environment of health support within the university community. Conclusion: health promotion strategies in an university context do not always result from the convergence between educational, political, legislative or organizational actions that support lifestyles and conditions which are favorable to the health of individuals or groups, and that contribute to improving the physical and social environment.